Hippocampus alterations in post-traumatic stress disorder among survivors of the consecutive Kahramanmaraş (Turkey) earthquakes in February 6, 2023: earthquake brain at the end of the first year - Olga Bayar-Kapıcı; Yaşar Kapıcı; Dilek Örüm; Mehmet Hamdi Örüm; Mehmet Şirik (BMC Psychiatry)
Abstract Background On February 6, 2023, a series of earthquakes resulted in approximately 60,000 deaths and 120,000 injuries in Turkey and Syria. These earthquakes caused serious psychological problems in addition to their social and economic effects. Post-traumatic stress disorder (PTSD) is one of the most frequently reported psychiatric disorder among the survivors of earthquakes. The aim of this study is to investigate the hemispheric asymmetries and volumes of hippocampus and amygdala of survivors under treatment with a diagnosis of earthquake-exposed PTSD (PTSD group) with earthquake-exposed subjects without a diagnosis of PTSD (non-PTSD group) one year after the Kahramanmaraş earthquakes. Methods PTSD subjects (n = 39, 17 females and 22 males) who had been using antidepressants for 6–12 months and matched (age, gender, education, smoking, menstrual cycle phase) non-PTSD subjects (n = 42, 21 females and 21 males) from hospital staff were retrospectively included in the study based on filtering criteria. Sociodemographic and clinical data were obtained through the patient registration system. The scores of the PTSD Checklist for Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Beck Depression Inventory, and Beck Anxiety Inventory administered to PTSD subjects and the Symptom Checklist-90-Revised (SCL-90-R) administered to all subjects at admission were recorded. Imaging of hippocampus and amygdala was performed with a 1.5-tesla MRI scanner and loaded into software that automatically analysed the segments. SPSS version 26.0 was used for the statistical analysis (descriptive, regression, correlation, receiver operating characteristic, multiple testing correction). A value less than 0.05 was considered statistically significant. Results While the groups were similar regarding history of major depressive disorder (p = 0.850) and anxiety disorder (p = 0.590), PTSD history in 1st degree relative (p = 0.005) and loss or injury of 1st degree relative in earthquake (p = 0.002) was higher in the PTSD group. The severity of psychiatric symptoms assessed with SCL-90-R was higher in the PTSD group than in the non-PTSD group (p < 0.001). Hippocampus and amygdala asymmetry was in favor of the left side in the PTSD group, while amygdala asymmetry was in favor of the right side in the non-PTSD group. After controlling for the effect of age in the PTSD group, a significant correlation was detected between total hippocampus volume and PCL-5 (r=-0.740, p < 0.001), SCL-90-R (r=-0.670, p < 0.001). According to the hierarchical binary logistic regression analysis, the sensitivity of age, gender, smoking status (block one) plus total hippocampus volume, amygdala asymmetry, loss or physical injury of 1st degree relative (block two) related to the determining the participants who was involved in PTSD and non-PTSD groups was 66.7%, and the specificity was 81.0% (Nagelkerke R2 0.363; Constant p = 0.040). Conclusions This study provides various results that volume and asymmetry parameters of hippocampus and amygdala may be associated with the presence of PTSD. Our study supports the information that stress exposure results in changes in hippocampus structure in PTSD. Longitudinal studies are needed to elucidate possible mechanisms.